IRF3-mediated pathogenicity in a murine model of human hepatitis A. - Lu Sun (Public Library of Science (PLoS), 2021)
HAV-infected Ifnar1-/- mice recapitulate many of the cardinal features of hepatitis A in humans, including serum alanine aminotransferase (ALT) elevation, hepatocellular apoptosis, and liver inflammation. Previous studies implicate MAVS-IRF3 signaling in pathogenesis, but leave unresolved the role of IRF3-mediated transcription versus the non-transcriptional, pro-apoptotic activity of ubiquitylated IRF3. Here, we compare the intrahepatic transcriptomes of infected versus naïve Mavs-/- and Ifnar1-/- mice using high-throughput sequencing, and identify IRF3-mediated transcriptional responses associated with hepatocyte apoptosis and liver inflammation. Infection was transcriptionally silent in Mavs-/- mice, in which HAV replicates robustly within the liver without inducing inflammation or hepatocellular apoptosis. By contrast, infection resulted in the upregulation of hundreds of genes in Ifnar1-/- mice that develop acute hepatitis closely modeling human disease. Upregulated genes included pattern recognition receptors, interferons, chemokines, cytokines and other interferon-stimulated genes. Compared with Ifnar1-/- mice, HAV-induced inflammation was markedly attenuated and there were few apoptotic hepatocytes in livers of infected Irf3S1/S1Ifnar1-/- mice in which IRF3 is transcriptionally-inactive due to alanine substitutions at Ser-388 and Ser-390. Although transcriptome profiling revealed remarkably similar sets of genes induced in Irf3S1/S1Ifnar1-/- and Ifnar1-/- mice, a subset of genes was differentially expressed in relation to the severity of the liver injury. Prominent among these were both type 1 and type III interferons and interferon-responsive genes associated previously with apoptosis, including multiple members of the ISG12 and 2'-5' oligoadenylate synthetase families. Ifnl3 and Ifnl2 transcript abundance correlated strongly with disease severity, but mice with dual type 1 and type III interferon receptor deficiency remained fully susceptible to liver injury. Collectively, our data show that IRF3-mediated transcription is required for HAV-induced liver injury in mice and identify key IRF3-responsive genes associated with pathogenicity, providing a clear distinction from the transcription-independent role of IRF3 in liver injury following binge exposure to alcohol.